Fabrication and Characterization of MWCNT Filled Hybrid Natural Fiber Composites. Issue 6 (2nd November 2017) - Mohan, K.; Rajmohan, T.
ABSTRACT: Hybrid composites are fabricated by the combination of two or more fibers using a single matrix. It can be fabricated either with all of its constituents as natural fibers or with one or more constituents belonging to artificial fiber. The stacking sequence of the fibers in a hybrid composite can be altered resulting in a varying mechanical properties. In the present study the MWCNT filled banana-jute-flax fiber reinforced composites are investigated for its mechanical behavior by varying the stacking sequence of the fiber layers and weight % of Multi-Walled Carbon Nano Tube (MWCNT). A Modified resin was prepared by adding MWCNT in the epoxy resin using ultrasonic probe sonicator and a hybrid composite is fabricated with it by using compression moulding processes. The mechanical properties are evaluated as per the ASTM standards. The incorporating of MWCNT and the stacking sequence of fiber layers shows the greater impact on the mechanical properties. The composites of jute fibers at the extremities (JBFBFBFJ) exhibiting the enhancement of tensile, compressive and hardness properties than the flax fiber at the extremities (FBJBJBJF) and it could be used in various automobile applications. Microstructure of the samples are investigated by Scanning Electron Microscope (SEM)with Energy dispersive X-ray (EDS). The results indicate that increasing the weight % of MWCNT and varying the stacking sequence of fibers improves the mechanical properties of hybrid natural fiber composites.